The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40468-016-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating washback to the learner from the IELTS test in the Japanese tertiary context

Abstract: Background: This study investigated the consequential validity of the International English Language Testing System (IELTS) Academic exam, specifically focusing on washback upon learners' test preparation strategies and score gain, and the mediating factors influencing washback when learners in an EFL context are not enrolled in test preparation courses. Methods: Two IELTS Tests were administered to 190 undergraduates at a Japanese university over a 1-year period. A survey instrument was used to collect data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 23 publications
10
42
0
Order By: Relevance
“…To date, a number of studies have investigated washback effects that large-scale proficiency tests have on language learning and teaching (Alderson and Hamp-Lyons, 1996;Allen, 2016;Cheng, 2004;Cheng, Klinger & Zheng, 2007;Green, 2007;Qi, 2004;Read & Hayes, 2003;Watanabe, 1996). For instance, researching courses offered in the private extracurricular institutions called yobiko (preparatory school), a type of school that prepared secondary school students for the English section of university entrance examinations, Watanabe (1996) examined the effect of the university entrance examination on the use of the grammar-translation method in Japan and found that the entrance examination failed to play a significant role in the choice of teaching methodology.…”
Section: Washbackmentioning
confidence: 99%
“…To date, a number of studies have investigated washback effects that large-scale proficiency tests have on language learning and teaching (Alderson and Hamp-Lyons, 1996;Allen, 2016;Cheng, 2004;Cheng, Klinger & Zheng, 2007;Green, 2007;Qi, 2004;Read & Hayes, 2003;Watanabe, 1996). For instance, researching courses offered in the private extracurricular institutions called yobiko (preparatory school), a type of school that prepared secondary school students for the English section of university entrance examinations, Watanabe (1996) examined the effect of the university entrance examination on the use of the grammar-translation method in Japan and found that the entrance examination failed to play a significant role in the choice of teaching methodology.…”
Section: Washbackmentioning
confidence: 99%
“…From the discussion of the four researches above, we can draw conclusion that the washback effect of IELTS test can be either positive and negative. The first research done by Allen (2016) indicates that IELTS test is beneficial for the learners' productive skill especially in speaking. They tend to focus on test-related tasks and materials when preparing for the test.…”
Section: Resultsmentioning
confidence: 99%
“…First discussion is talking about the journal article written by Allen (2016). This article entitles investigating washback to the learner from the IELTS test in the Japanese tertiary context.…”
Section: First Articlementioning
confidence: 99%
“…Positive washback effects of 4SETs have also been reported. One example is positive washback on students' learning of productive skills by introducing IELTS in a university in Japan (Allen, 2016). Increasing to have a more communicative focus by introducing 4SETs as university entrance examinations can have positive washback effects on high school English teachers' instruction (Hama and Okabe, 2016).…”
Section: Possible Positive and Negative Washback Of Introducing 4setsmentioning
confidence: 99%